DETERMINANT FACTORS OF HOSPITALS PRICES WITH INA-CBGS PRICES FOR THYPOID FEVER (Journal of Hospital Management, 2018)
Thypoid fever was first rank of the top 10 disease hospitalizations at An-nisa Hospital. Still founded differences between hospitals price and INA-CBGs price, which can be impact to hospitals finance. The purpose of this study is to analyse determinant between hospitals price and INA-CBGs price and analyse influence factor of hospitals price. The study focus was hospitalize of thypoid fever without complication at An-nisa Hospital. Research design is corelational-comparatif study. The number of sample was 320 medical record. Normality test was analyse with kolmogorov-smirnov test, correlational was analyse with spearman test and comparative test with wilcoxon test. The result showed that founded differences between hospitals price and INA-CBGs price, specially at medical fee, drugs cost, and others cost. The significant differences caused by difference way to count price, Hospitals price was based on unit cost. Meanwhile, INA-CBGs price was count by mean hospitals price from certain hospital. The result also founded correlation between accomodation, others cost, medical fee, drugs cost and supporting examination with hospitals price. The implication of this study is need more control of clinical pathway implementation, periodic audit of clinical pathway implementation and maximised function of case manager to cost control dan quality control of healthcare service.Keyword : Determinant factors, Hospitals price, INA-CBGs price, demam tifoid